Factors associated with poor appetite among residents at selected long-term care facilities in Selangor, Malaysia - Al-junid, Duaa; Chan, Yoke Mun; Adznam, Siti Nur Asyura; Chin, Yit Siew; Mohd Shariff, Zalilah; Lim, Poh Ying; Shariff-Ghazali, Sazlina; Rosli, Tanti Irawati (Malaysian Journal of Nutrition, 2024)
Introduction: Poor appetite is prevalent among older adults and may negatively impact on their overall health. This is especially true for institutionalised residents. Despite this, there is a paucity of research on appetite and its associated factors among institutionalised residents, which signified the present study. Methods: A cross-sectional study was conducted among elderly residents at long-term care facilities in the state of Selangor, Malaysia to ascertain their appetite status and its associated factors. Results: A total of 97 residents with mean age of 74.2±8.4 years old were recruited. They comprised 61.9% females and 38.1% males. More than 50% had poor appetite with early satiety. There were 63.0%, 82.4%, and 94.8% who had poor oral health, poor sleep quality, and depression, respectively. Ethnicity (OR=2.73; 95% CI=1.00-7.44; p=0.049) was the only factor that predicted poor appetite among older adults in long-term care facilities, with Malay residents having poorer appetite than their Chinese and Indian counterparts. Conclusion: The prevalence of poor appetite was high among residents staying at long-term care facilities in Selangor, Malaysia, especially among Malays. This issue deserves further studies to identify the specific underlying factors contributing to poor appetite among older adults from different ethnicities. Acknowledging the high prevalence of poor appetite among older adults and its possible unfavourable outcomes, appropriate nutrition interventions are therefore needed to address this issue among institutionalised elderly.